Customer Experiences in Mindful Consumption of Organic Food : Convergent Parallel Mixed Method - Sripathi, Madhavi; Prasad, U. Devi; Leelavati, T. S. (Indian Journal of Marketing, 2025)
Purpose : This study examined the impact of mindful consumption on customer experiences in the organic food market. With health and sustainability becoming more important—especially after the COVID-19 pandemic—it was essential to understand how consumers viewed and interacted with organic food. The research examined how health orientation, sustainable attitudes, and mindful living impacted purchasing decisions. Methodology : A convergent mixed-methods research approach was adopted to collect data from 850 respondents using a structured questionnaire. Structural equation modeling (SEM) was employed for the quantitative analysis, and customer journey mapping was used to capture qualitative insights. Such an approach enabled an extensive investigation of how different dimensions of mindful consumption [i.e., health orientation, sustainability, and conscious living] influenced customer experience and purchasing behavior. Findings : The findings indicated that health orientation, sustainability, and shopping convenience had a significant impact on customer experience. Furthermore, store layout and features were important determinants of whether they would intend to make a purchase. These results highlighted the role of mindfulness in the experiences of consumers with organic food. Practical Implications : These revelations could offer businesses and marketers a new way to refine their tactics in accordance with the growing demand from mindful consumers. Through advocacy for the health, environmental, and convenience benefits of organic food, the industry could drive growth in the organic food market. Originality : This study developed a comprehensive theoretical model that links mindfulness consumption to customer experience. Filling the gaps of research led to the discovery of new aspects of (previously recognized aspects of) the relationship between mindful consumption and consumer decision-making in the organic food market, making both the academic investigation and practical marketing more useful.